2022
DOI: 10.1108/ijchm-12-2021-1524
|View full text |Cite
|
Sign up to set email alerts
|

Perceived price and trustworthiness of online reviews: different levels of promotion and customer type

Abstract: Purpose Prior hospitality studies have reviewed review trustworthiness and perceived price as predictors of restaurant selection. However, the impacts of these two factors may vary by sales promotion and customer types. This study aims to determine whether sales promotions and customer type are the key elements that facilitate behavioral intentions by moderating the linkage between perceived price and behavioral intentions as well as the linkage between online review trustworthiness and behavioral intentions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 91 publications
1
17
0
2
Order By: Relevance
“…For example, a DL model for detecting deceptive reviews driven by DCWord (Deep Context representation by Word vectors) (Zhang et al , 2019d), a deep-learning-based sentiment analysis model that integrates two-channel CNN–LSTM models, combining CNN and LSTM/BiLSTM branches in a parallel manner (Li and Law, 2020). Besides, the application of text mining for tourist reviews has also been explored (Liu et al , 2022; Pan et al , 2022). In conclusion, the studies classified under this theme have mainly focused on the application of DL towards enhancing the state-of-the-art in two main areas – demand forecasting and sentiment analysis (refer to Table 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a DL model for detecting deceptive reviews driven by DCWord (Deep Context representation by Word vectors) (Zhang et al , 2019d), a deep-learning-based sentiment analysis model that integrates two-channel CNN–LSTM models, combining CNN and LSTM/BiLSTM branches in a parallel manner (Li and Law, 2020). Besides, the application of text mining for tourist reviews has also been explored (Liu et al , 2022; Pan et al , 2022). In conclusion, the studies classified under this theme have mainly focused on the application of DL towards enhancing the state-of-the-art in two main areas – demand forecasting and sentiment analysis (refer to Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…In our study sample, 28 of 159 articles (18%) applied DL for sentiment analysis (see (Li and Law, 2020). Besides, the application of text mining for tourist reviews has also been explored (Liu et al, 2022;Pan et al, 2022). In conclusion, the studies classified under this theme have mainly focused on the application of DL towards enhancing the state-of-the-art in two main areas -demand forecasting and sentiment analysis (refer to Table 5).…”
Section: Taxonomy Of Hospitality Travel and Tourism (Htt) Literature ...mentioning
confidence: 99%
“…Penelitian ini sejalan dengan penelitian sebelumnya (Pan et al, 2022) dari preferensi konsumen bergantung pada apakah mereka dapat mempercayai informasi positif, negatif, atau netral yang mereka terima dari ulasan. Namun, ulasan pelanggan bervariasi dari orang ke orang.…”
Section: Trustworthiness Of Online Reviews Secara Positif Memengaruhi...unclassified
“…Penelitian ini tidak sejalan dengan penelitian sebelumnya dari (Pan et al, 2022) bahwa Jika konsumen bersedia menerima harga menu suatu restoran, maka persepsi harga akan berpengaruh positif terhadap kesediaan mereka untuk berkunjung ke restoran tersebut. Dalam hal ini, sebuah studi berbasis skenario menemukan bahwa pelanggan yang menganggap kenaikan harga dapat diterima memiliki niat kunjungan yang positif.…”
Section: Perceived Price Secara Positif Mempengaruhi Behavior Intentionunclassified
“…General promotion approaches, such as cash discounts, coupons, and other conventional means of promotion (Peng et al, 2019;Sinha and Verma, 2020; 10.3389/fnins.2022.938511 Kotler et al, 2021), can be frequently observed throughout the year. However, these promotion approaches have become so ordinary that they lack attraction for consumers, who have gradually become familiar with the basic marketing logic of these methods (Amornpetchkul et al, 2018;Pan et al, 2022). It is difficult to say whether a wide range of general promotion activities will be successful; even if so, they may require a huge advertising budget.…”
Section: Introductionmentioning
confidence: 99%